2013
DOI: 10.1371/journal.pone.0079938
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Hyperschematia without Spatial Neglect after Insulo-Thalamic Disconnection

Abstract: Different spatial representations are not stored as a single multipurpose map in the brain. Right brain-damaged patients can show a distortion, a compression of peripersonal and extrapersonal space. Here we report the case of a patient with a right insulo-thalamic disconnection without spatial neglect. The patient, compared with 10 healthy control subjects, showed a constant and reliable increase of her peripersonal and extrapersonal egocentric space representations - that we named spatial hyperschematia - yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We know of a case of spatial hyperschematia, compatible with AIWS symptoms, in a patient with a lesion disconnecting the thalamus from right parietal and temporal cerebral cortices as well as the insula [38]. …”
Section: Aiws As An Alteration Of Visual and Somatosensory Integramentioning
confidence: 99%
See 1 more Smart Citation
“…We know of a case of spatial hyperschematia, compatible with AIWS symptoms, in a patient with a lesion disconnecting the thalamus from right parietal and temporal cerebral cortices as well as the insula [38]. …”
Section: Aiws As An Alteration Of Visual and Somatosensory Integramentioning
confidence: 99%
“…A case of spatial hyperschematia without spatial neglect was described after an ischemic lesion causing a disconnection between the right insula and the posterior part/pulvinar of the thalamus [38]. In this subject, an extension of peripersonal and extrapersonal space, especially from the egocentric point of view, was observed.…”
Section: Aiws and Migrainementioning
confidence: 99%
“…A similar change in VAN lateralization was shown to occur in neglect patients after right hemispheric lesions [30]. Second, tasks known to rely on DAN, such as line bisection or visual search, yielded greater activation within DAN after R-PA, as shown in patients with neglect [32]. Both types of changes in the organization of the attentional system occur very rapidly, over a few minutes, and reflect thus functional reorganization rather than structural changes [20].…”
Section: Introductionmentioning
confidence: 59%
“…alleviate neglect symptoms [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]64], predominantly in patients with anterior lesions in whom the posterior part of the corpus callosum and the right DAN are spared [50,65,66]. Activation studies have demonstrated that R-PA induces in neglect patients a shift of dominance by establishing ipsilateral spatial representation within VAN on the left side [30] and that it increases responsiveness of DAN [32]. Thus, there are similarities in R-PA induced effects between normal subjects and patients with neglect, but several aspects have not yet been investigated.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation